MODERN CONCEPTS REGARDING THE INFLUENCE OF PSYCHO-EMOTIONAL STATE AND PERSONAL FEATURES ON SUCCESSFUL INSTALLATION OF DENTAL IMPLANTS - Vladimir B. Gritsayuk (Вестник Северо-Кавказского федерального университета, 2022)
The article dwells on the current understanding of the psycho-emotional state and individual personal features; there is also a view presented on personality and behavior disorders, and the types of neuroses.